Training and Assistance for Goat Breeders in Compiling the Cost of Production - Winda Hurotul'Aini; Rifka Arinda Noviasari; Sari Narulita; M Iswahyudi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
This service activity is carried out with the aim of providing training and assistance to goat breeders (K-Milk Farm) in Kalipuro Village in compiling and making the cost of production. The cost of production helps farmers to be able to independently calculate how much production costs are incurred which can then be used as a basis for calculating business profit and loss, even though the price for livestock products in the form of milk is determined by the market. The method of implementing community service is carried out by providing training in classifying the costs incurred by breeders. Variable costs, fixed costs and semi-variable costs. After the classification is carried out, training is given related to the calculation and preparation of the cost of production. Not only training, this service is also followed by mentoring activities aimed at maintaining communication and consultation between the service team and breeders. The results of the service show that farmers so far have not separated the costs used for production and non-production purposes. So to make the cost of production free from bias it is necessary to separate costs.